Altruism and Welfare Practices of Pempek Cek Ayu in Micro MSME Business - Joyo Pramudya; Oktaviana, Rina; Misnawati, Desy; Maharani, Dwi (Indonesian Journal of Advanced Research, 2024)
In the era of globalization, MSME micro businesses have unique opportunities and challenges. Business sustainability is a critical focus, with an emphasis on environmentally friendly practices, economic resilience and social responsibility. Along with this, technology and global connectivity play a significant role in increasing visibility and market access for micro businesses. Although many MSME micro businesses face obstacles, such as limited access to capital and human resources, research findings show that innovation and adaptability are the keys to success. Micro businesses that are able to adopt technology, understand global markets, and respond to changing trends have the potential to grow and have a positive impact. The sustainability of MSME micro businesses is also closely connected to local empowerment. Overall, this research provides a comprehensive view of MSME micro businesses as important agents in the local and global economy. It is hoped that these findings can provide guidance for stakeholders, including business owners, governments and supporting organizations, to improve a sustainable and competitive micro-business environment amidst global challenges. This article presents a solution to help the development of MSMEs by forming a special institution consisting of lecturers and communication science students from Bina Darma University who continuously dedicate themselves to MSMEs to create and manage brands and the quality of human resources in order to build prosperity between owners and employees.